2013
DOI: 10.1002/bsl.2074
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning Between Systems of Care: Missed Opportunities for Engaging Adults with Serious Mental Illness and Criminal Justice Involvement

Abstract: Individuals with serious mental illness are overrepresented in the criminal justice system and face difficulties accessing mental health services both during incarceration and upon re-entry into the community. This study examines how such individuals describe their experiences receiving care both during and after their time in custody and explores the perspectives of mental health service providers who treat this population upon re-entry. Semi-structured interviews were conducted with 43 individuals identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…In addition to mental health service use, other needs must be addressed to avoid repeated criminal justice involvement. Safe housing, substance abuse support for those with dual diagnoses, job support, and education can support successful reentry . As availability of these services varies between contexts, the apparent association between mental health service use and criminal justice outcomes may also vary.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…In addition to mental health service use, other needs must be addressed to avoid repeated criminal justice involvement. Safe housing, substance abuse support for those with dual diagnoses, job support, and education can support successful reentry . As availability of these services varies between contexts, the apparent association between mental health service use and criminal justice outcomes may also vary.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…Addressing the co-morbidities of mood disorders and addictions has long been known to constitute an important priority for correctional health programming that has implications for reduced rates of reentry (67), and addressing these factors is considered to be important for reduced STI/HIV risk (44, 55). There remains a need to strengthen substance use treatment in corrections (55) while mental health services and discharge planning within correctional facilities currently are inconsistent and inadequate (68, 69). When addressing substance use in the context of STI/HIV prevention among inmates, programming should be tailored for older versus younger inmates given the dramatic cohort differences in drug use observed.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Studies have identified many predictors of treatment disengagement including demographic factors (e.g., younger age, male gender), clinical factors (e.g., co-occurring substance abuse, poor awareness of symptoms), and service use (e.g., prior history of treatment discontinuation). 1,3 Treatment providers are challenged to establish effective therapeutic relationships with clients with serious mental illness because of common complicating factors including impaired awareness of symptoms, 5 co-occurring substance abuse, 6 housing instability, 7 criminal justice involvement, 8,9 unemployment, 10 and stigma. 11,12 Despite and perhaps because of these challenges, effective therapeutic relationships are key predictors of symptom, functional, and service use outcomes in this population.…”
Section: Introductionmentioning
confidence: 99%